MORPHOLOGICAL FEATURES OF THE UZBEK LANGUAGE - Bozorov Behruz Ilhom oʻgʻli (Bright Mind Publishing, 2025)
This article discusses various dialects found among the people, their uniqueness, their place and significance in the Uzbek language. It discusses the relationship of the Uzbek literary language to dialects, their place in the language system, and the state of their use among the people.
Keywords: Linguistics, Uzbek language, dialects, lexis, dialectics, literary language, dialect, meaning, lexical.